2021
DOI: 10.3390/w13202857
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nano- and Small Microplastics on Ciliated Protozoan Spirostomum ambiguum (Müller, 1786) Ehrenberg, 1835

Abstract: This study evaluated the uptake of secondary nano- and small microparticles by the protozoan Spirostomum ambiguum, comparing edible (baker’s yeasts) and inedible (red latex) particles. Secondary nano- and microplastic particles were prepared from household materials made of four different polymers and served to the protozoans separately and as two-component mixtures in different proportions. The number and content of food vacuoles formed by the protozoan were analyzed using a digital microscope. The microscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…Furthermore, Davarpanah and Guilhermino ( 2015 ) measured the specific mean growth rate of the green alga Tetraselmis chuii and found no significant effects of MPs. In contrast, in the present study, the population growth rate was significantly lower at low concentrations of beads compared to both the control and high concentrations, suggesting a negative effect of MPs on the viability of these species, in contrast to the previous findings of Nałęcz-Jawecki et al ( 2021 ), who described a possible negative effect of nanoparticles on vacuole formation in S. ambiguum only when the toxicity threshold was exceeded. These conflicting results may be due to differences in particle concentrations, type of MPs or different ciliate species used in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Davarpanah and Guilhermino ( 2015 ) measured the specific mean growth rate of the green alga Tetraselmis chuii and found no significant effects of MPs. In contrast, in the present study, the population growth rate was significantly lower at low concentrations of beads compared to both the control and high concentrations, suggesting a negative effect of MPs on the viability of these species, in contrast to the previous findings of Nałęcz-Jawecki et al ( 2021 ), who described a possible negative effect of nanoparticles on vacuole formation in S. ambiguum only when the toxicity threshold was exceeded. These conflicting results may be due to differences in particle concentrations, type of MPs or different ciliate species used in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Microplastic particles, measuring approximately 1–2 µm in size, can be ingested unintentionally or accidentally by ciliates and transferred to higher trophic levels, when protists are ingested by crustacean zooplankton and other small organisms, thus linking all parts of the food web (Cole et al 2013 ). However, some filter-, suspension-, and detritus-feeding ciliates living in water and sediments have been observed to intentionally ingest MPs in laboratory experiments (Nugroho and Fyda 2020 ; Nałęcz-Jawecki et al 2021 ; Bulannga and Schmidt 2022 ). Some ciliates that exhibit the above consumption modes may feed on bacteria, suspended organic matter, or small algae but may also graze on fine inorganic particles (Bernard and Rassoulzadegan 1990 ; Pierce and Turner 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…NPs are also suitable for biofilm formation [16]. Scientific studies have shown that MP and NP have minimal impact on various species such as yeast, bacteria, and protozoa [17,18]. Various toxicological effects on organisms such as invertebrates, vertebrates, seabirds, and mammals were also discussed [19][20][21].…”
Section: Figure 1 -Degradation Of Plastics In Aquatic Environments Fr...mentioning
confidence: 99%
“…MPs were prepared from everyday products such as PS from the black side of a CD box, PET from a red bottle of ketchup, PVC from a tap water pipe, and PhR from laboratory worktops. The materials were prepared according to the procedure described in our previous paper [28]. MP stock suspensions (4 g L −1 of Tyrode's solution) were homogenized using an ultrasonic water bath (Polsonic, type Sonic 6, Warsaw, Poland) for 20 min at room temperature.…”
Section: Microparticlesmentioning
confidence: 99%